Solid waste collection and disposal problems : a case study of Klang Valley and Johor Bahru, Malaysia - 190550 Lokman Md. Hani; Fadil Othman; International Conference on Solid and Hazardous Waste Management (1991 : Singapore) ([s l] : [s n], 1990)
10